Dermatophytosis in patients referred for evaluation at a tertiary care teaching hospital in Kashmir, India - Ahmad, Mansoor; Nazir, Aanisa; Khursheed, Syed; Mir, Suraiya; Shafi, Azhar (International Journal of Research in Medical Sciences, 2022)
Background: Dermatophytoses invade the stratum corneum of the skin and other keratinized tissues derived from the epidermis. They are quite common and can be fairly accurately identified by a simple laboratory test. We conducted this study to identify the common dermatophytic infections in our setting. Methods: Clinically suspected tinea infections were referred to the Department of Microbiology of SKIMS Medical College Hospital, a tertiary-care teaching hospital in Srinagar, Kashmir. The affected area was cleaned with 70% alcohol, and scrapings were obtained. 10% KOH was used for keratinolysis. Samples were thoroughly examined for the presence of filamentous, septate, branched hyphae. Results: A total of 206 samples were analyzed. The overall KOH positivity rate was 44.7%. Of the 206 patients, 119 (57.8%) were males, and 142 (68.9%) resided in rural areas. The mean age of the patients was 32 years (range 4-72). Tinea corporis was the typical clinical manifestation (58.3%). Conclusions: Young and middle-aged males and people living in rural areas are at a higher risk of dermatophyte infections.